Segmentation of local food consumers based on altruistic motives and perceived purchasing barriers: a Croatian study. Issue 1 (1st January 2021) - Mesić, Željka; Petljak, Kristina; Borović, Darija; Tomić, Marina
Abstract: This is the first empirical study which has segmented consumers based on their altruistic motives and perceived barriers in purchasing local food in a developing country, which has received little prior research attention and as such, provides a valuable contribution to the local food research stream. An empirical study was conducted via an online questionnaire on a sample of 402 Croatian local food consumers. In such a way we identified two consumer segments: (1) embedded local food consumers and (2) disinclined local food consumers . Embedded local food consumers report a significantly higher mean score concerning altruistic motives and a significantly lower mean score for perceived barriers in purchasing local food compared to the other segment. Also, they buy and consume local food more often and put more emphasis on personal motives, such as freshness, quality, and taste. Embedded local food consumers are more satisfied with the current local food supply and are willing to pay higher prices for local food as compared to disinclined local food consumers . This empirical study fills the evident research gap in local food literature regarding altruistic motives and barriers in purchasing locally produced food.